Deep Venous Thrombosis after Ad26.COV2.S Vaccination in Adult Male - Habiba Hussain; Matthew Sehring; Sheryll Soriano (Case Reports in Critical Care)
With extensive loss of life and well-being seen since the beginning of the SARS-CoV-2 pandemic, the initiation of vaccinations has come with enormous hope towards the end of this pandemic. Detailed discussions regarding the safety and efficacy of these vaccines led to their approval. With such success, there have also been reports of vaccine-associated adverse events—allergic reactions, anaphylaxis, immune thrombocytopenia, and thrombosis. We discuss and report the first case of a healthy young adult male developing extensive thrombosis, after receiving the Ad26.COV2.S (Johnson & Johnson/Janssen) vaccine.